Is it possible to transform $f(x)=x^2+4x+3$ into $g(x)=x^2+10x+9$ by the given sequence of transformations?

Is it possible to transform $f(x)=x^2+4x+3$ into $g(x)=x^2+10x+9$ by the transformations

\[f(x) \rightarrow x^2 f(1+\frac{1}{x})    or   f(x) \rightarrow (x-1)^2f(\frac{1}{x-1})?\]

Answer

Answers can be viewed only if
  1. The questioner was satisfied and accepted the answer, or
  2. The answer was disputed, but the judge evaluated it as 100% correct.
View the answer
The answer is accepted.